College Student Perceptions of the Root Causes of Sexual Violence Before and After a Curricular Intervention - Liddell, Jessica L. (Violence against women, 2024)
Campus sexual violence is prevalent and consequential. After a climate survey at our university revealed high rates of sexual violence, a semester-long academic course was designed as a curricular intervention for first-year students. This study examines an assignment completed at the beginning and end of the course. Students were asked: “What are the root causes of sexual violence?” Thematic analysis of papers revealed that many students altered or expanded their thinking to more complex, structural factors compared to their initial perceptions. An academic course may broaden students’ understanding of the determinants of sexual violence.